LANDAU–KLEFFNER SYNDROME (ACQUIRED EPILEPTIC APHASIA) WITH A FOCUS ON ELECTROENCEPHALOGRAPHIC CRITERIA - K. Yu. Mukhin (Русский журнал детской неврологии)
Landau–Kleffner syndrome (LKS) is a disease from the group of age-dependent epileptic encephalopathies with the phenomenon of prolonged spike–wave activity in slow-wave sleep, which is manifested by acquired sensorimotor aphasia, impaired higher mental functions concurrent with various epileptic seizures and diffuse electroencephalographic (EEG) epileptiform changes in the absence of cerebral structural changes. In 1957, W. M. Landau, a pediatric neurologist, and F. R. Kleffner, a logopedist, first described the clinical presentation of the disease in 6 patients. The author associated the occurrence of aphasia with epileptiform EEG activity rather than with epileptic seizures, i. e. they per se formulated the modern concept of epileptic encephalopathy. There has been currently evidence that prolonged diffuse epileptiform activity has a damaging effect on a child’s developing brain, which is seen in impairments of speech and other higher mental functions. The age of patients with manifestations of LKS (3–5 years) is a critical period for the development of speech function. According to the concept of H. Doose (2003), congenital brain maturation disorder underlies LKS. The paper considers ideas on the origin of the LKS, including the possible genetic bases of diseases, epidemiological aspects, clinical and EEG manifestations with a detailed description ictal and interictal EEG changes, and treatment approaches, including the author’s data. The disease is characterized by an electroclinical triad: seizures (may be absent or may be single in a history), impaired higher mental functions (with a predominance of aphasic disorders), epileptiform EEG activity (a combination of regional and diffuse patterns with an increase during sleep).